Mapping research trajectories on didactics and praxeology in mathematics education: A bibliometric analysis - Nurhaeni, Puput Indiriyani; Ismayanti, Syifa; Utami, Wulan Putri; Hartanto, Ahmad Iqbal (Papanda Publisher, 2024)
This study presents a bibliometric analysis of research on didactics and praxeology in mathematics education between 2007 and 2024. Drawing on 312 Scopus-indexed publications, the analysis maps publication trends, citation performance, thematic clusters, and country-level contributions. Findings reveal three phases of research development: early epistemological debates (2007–2012), expansion into teacher education and professional development (2013–2018), and a recent focus on didactical design, learning obstacles, and cultural relevance (2019–2024). Citation indicators highlight foundational works by Chevallard, Straesser, and Winsløw, alongside emerging contributions linking theory to classroom practice. Thematic cluster analysis identifies four main domains: didactic foundations, teacher education, learning processes, and equity in mathematics education. Geographically, Europe remains the intellectual hub, but growing contributions from Indonesia, Brazil, and South Africa signal increasing global diffusion. The study concludes that didactics and praxeology have evolved into a legitimate and dynamic research domain that bridges theoretical discourse with practical applications, offering implications for researchers, teacher educators, policymakers, and classroom practice